You Say you Want a Revolution? a Case study of MP3.com - Burke, Andrew; Montgomery, Chris (Senate Hall, 2003)
MP3.com was a revolutionary venture set up in an attempt to break the mold of the music recording industry. The case study documents the venture's impressive growth and the factors affecting its performance. A deep understanding of the case requires the reader to draw from a wide spectrum of economics, new venture management theory, and both antitrust and copyright laws.
Keywords: music industry|dot.com venture|new venture economics|copyright law